2023
DOI: 10.3389/fenvs.2023.1119246
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the digital economy on carbon emission intensity: Evidence from China

Abstract: Evaluating the impact of the digital economy on carbon emission intensity has great significance in promoting sustainable development. Based on the panel data of 30 provinces in China from 2013 to 2019, the level of the digital economy is estimated by using entropy weight and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) model. The panel vector auto-regressive (PVAR) model is used to analyze the impact of the digital economy on carbon emission intensity. The results show that, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…In this regard, several studies have explored the impact of AI on the intentionality of carbon emissions, particularly in the context of China and especially in large cities with advanced technology and infrastructure [34]. Chen et al [35] found that AI significantly reduces carbon intensity, with the latter emphasizing the role of AI in optimizing industrial structure and fostering green technology innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, several studies have explored the impact of AI on the intentionality of carbon emissions, particularly in the context of China and especially in large cities with advanced technology and infrastructure [34]. Chen et al [35] found that AI significantly reduces carbon intensity, with the latter emphasizing the role of AI in optimizing industrial structure and fostering green technology innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This seems inconsistent with the real situation of the development of the digital economy. Shahbaz et al used the entropy method to measure the digital economy index in four areas: infrastructure, social impact, digital trade, and social support, which more fully reflect the areas covered by the digital economy [29]. And the full array polygon graphic index method was used to measure the digitization level in the study by Ren et al Of course, there are also studies that use the Entropy-TOPSIS model to construct a digital economy model from both input and output perspectives.…”
Section: The Literature Context Of the Digital Economymentioning
confidence: 99%
“…Xu hướng lớn thứ hai là sự phát triển của kinh tế nền tảng khi thế giới đã trải qua một giai đoạn đổi mới công nghệ dựa trên Internet và nền kinh tế toàn cầu đã bước vào một giai đoạn phát triển kinh tế kỹ thuật số mới. Hơn nữa, những lợi ích mà nền kinh tế kỹ thuật số mang lại trong đó có thúc đẩy tăng trưởng việc làm đã trở thành mối quan tâm kinh tế và chiến lược lớn mà tất cả các nền kinh tế phải đối mặt khi nền kinh tế kỹ thuật số trên toàn thế giới bước vào giai đoạn phát triển nhanh chóng [30].…”
Section: Sự Phát Triển Kinh Tế Nền Tảng (Platform Economy)unclassified